PERAN PEMERINTAH DESA DALAM PEMBERDAYAAN MASYARAKAT PETANI DI DESA KERTAMUKTI KECAMATAN CIBITUNG KABUPATEN BEKASI - Muhammad Viki Nisfani Al Azis (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2022)
Empowerment has a process to be efficient so that it can change the community for a better condition. Through the role of the village government, empowerment of the farming community is carried out in order to promote the welfare of the farming community's living standard and economics. The purpose of this research is to find out how the role of local government as a regulator, dynamizer, facilitator, and catalyst in empowering farming Communities in Kertamukti Village, Cibitung District, Bekasi Regency. This study uses a descriptive method with a qualitative approach. Data were analyzed through interview techniques, documentation and direct observation to the field. The result of this research is that the role of the Kertamukti Village Government is quite good, although it is not optimal in the role of facilitator and catalyst in terms of the village government's lack of attention to capital assistance for farming communities in Kertamukti village.